Citizen Participation in Responding to Natural Disasters Through Twitter Messages - Pamuji, Rizky; Aknuranda, Ismiarta; Ramdani, Fatwa (Faculty of Computer Science (FILKOM) Brawijaya University, 2020)
Citizen participation in collect and distribute information increase the role of the citizen involvement in local issues and increasing the benefits of society for the government and the environment. The contribution of citizens can be useful in helping to deal with environment problems and assist certain parties in meeting data needs, this is commonly referred to as citizen science. In its development, citizen science involvement in providing information began to involve social media as a platform for sharing information. In this study we try to explore citizen science of Indonesia, we conduct case study exploring how citizen in Indonesia used social media such as Twitter in response to one of the country’s worst disaster in 2018 namely Lombok Earthquake. By analyzing these user generate message we may know what the response of Indonesian citizen during event and understand more about citizen science in Indonesia through social media including its role and contribution. The information also may assist local communities in obtaining up-to-date information, providing assistance according to needs of the populace and use to manage and plan disaster relief both during and after the event.